RISKS SPECIFIC TO RA UNIVERSITIES ACCORDING TO IMPACT LEVELS (EDUCATION IN THE 21ST CENTURY, 2023)
The purpose of the research is to present the main risks in RA universities based on the studies of statutes, strategic plans of RA state universities, self-analysis of institutional capabilities and expert reports. The management of the institutions in RA universities is carried out on the basis of self-governance, combining the principles of sole management and collegiality, with the implementation of the functions of the board, the scientific board and the rectorate. The governing bodies of the university are:• board of trustees/management• the rector/manager/director/executive body.In general, the charter of universities stipulates that the university's highest management and control body is the university's board of trustees, which supervises the university's activities, including the financial and economic activities, as well as the selection of the person who audits the financial statements.The novelty of the research is the proposed risks in RA universities, which were brought out as a result of the analysis of the documents proposed in the article.Analyzing the provisions in the strategic programs of RA universities, it can be noted that RA universities mainly single out corruption risks from the factors affecting their activities, for the reduction of which various mechanisms and anti-corruption programs are developed. However, there is no reference to other types of risks in strategic plans, and corruption risks are general and are not separated according to the forms of manifestation, for example, bribery, embezzlement, extortion, nepotism. In addition, although the statutes and strategic plans of the universities provide for certain actions aimed at control, there is no separate internal control and risk management toolkit, the internal control actors, responsible bodies and units are not specified.
Keywords: university risk management; human resources; financial risks; schedule risks